Aspects of Legislative Protection for Sustainable Development in Iraqi Civil Law : An Analytical Study - Abdul Qader, Ali; Abdul Razzaq, Muhammad (Journal of Legal Sciences, 2025)
Sustainable development is one of the modern concepts that seeks to achieve a balance between the requirements of economic growth, social justice and environmental protection, so that the needs of the present generation are met without harming the rights of future generations. Although the Iraqi Civil Law No. (40) of 1951 was established before the emergence of this concept globally, its texts and general principles include aspects that indirectly contribute to achieving the goals of sustainable development. Accordingly, this research addresses the aspects of sustainable development in Iraqi civil law through three main dimensions, namely the economic, social and environmental dimensions.